Analysis Of The Effect Of Digital Marketing In Increasing Public Interest In The Urology Polyclinic Of Al-Muchtar Islamic Hospital, Karawang - Ade Putra; Aliefety Putu Garnida; Yaya Aria Santosa; Rasyiqah Saratiana; Dinni Agustin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
Background: Al-Muchtar Islamic Hospital Karawang faces challenges in increasing public interest in its urology clinic, which recently reopened after a temporary closure. Amid intense competition, high service quality demands, and technological advancements, digital marketing becomes a crucial strategy to restore public trust, boost visits, and ensure the sustainability of quality urology services. Method: This quantitative study uses a cross-sectional approach, analyzed with simple logistic regression for bivariate and multiple logistic regression for multivariate analysis. Data were collected through written questionnaires and literature studies during December 2024–January 2025, with a sample of 90 respondents. Results: There is a significant influence of gender on interest in the urology clinic (p-value = 0.017), content (p-value = 0.032), accessibility (p-value = 0.016), and customer engagement (p-value = 0.033) at Al-Muchtar Islamic Hospital Karawang. Gender has a minor influence on interest in the urology clinic (OR: 0.227; 95% CI: 0.067–0.766). Content (OR: 12.726; 95% CI: 1.239–130.701) and accessibility (OR: 8.772; 95% CI: 1.487–51.752) significantly increase interest, while customer engagement (OR: 0.019; 95% CI: 0.001–0.729) has a smaller influence. Conclusion and Sugestion: Gender, content, accessibility, and customer engagement significantly influence interest in the urology clinic at Al-Muchtar Islamic Hospital Karawang, with content and accessibility being the primary factors. Improving digital marketing requires strengthening teams, training, providing necessary tools, ensuring accessibility, implementing follower growth strategies, and coordinated promotion efforts.